LAYANAN BIMBINGAN KELOMPOK TEKNIK ROLE PLAYING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 6 BANJARBARU - Yulian, Rika Wulan; Irhamni, Irhamni; Fauzi, Zainal (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
The task of teacher guidance and counseling in schools is to deal with problems related to physical and psychological that occur in students in school, especially student behavior including student learning motivation. The purpose of the study is to determine the level of student motivation by using role playing methods , and to find out what factors can increase student learning motivation. The research method used is descriptive with a case study of an event presented in the form of role playing. The results of the study showed that in the first stage there was no learning motivation for group members. Stage 2 there are still some who are still joking in role playing. Stage 3 has got positive results, only some of the group members have not followed the guidance properly. Stage 4 has got positive results because all group members followed the guidance well, all students were active and enthusiastic following the last guidance given. Through this stage 4 guidance service, the group members' learning motivation has been seen. The conclusion of this study is that there is an increase in student learning motivation through 4 stages by using role playing techniques . Suggestions from this study are that teachers pay more attention to students whose motivation is less in terms of learning in school and for students to be more enthusiastic to learn.